Still different after all these years: Extensive and intensive margins of exports in East and West German manufacturing enterprises - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This paper uses a new tailor-made data set to investigate the differences in extensive and intensive margins of exports in manufacturing firms from East Germany and West Germany. It documents that these margins do still differ in 2010, 20 years after the re-unification of Germany. West German firms outperform East German firms at all four margins of exports - they have a larger propensity to export, export a larger share of total sales, export more goods and export to a larger number of countries. All these differences are large from an economic point of view. A decomposition analysis shows that in 2010 between 59 percent and 78 percent of the difference in margins can be explained by differences in firm characteristics. Most important here is the higher human capital intensity and (to a much lesser extent) the larger share of old firms in West Germany compared to East Germany.
Keywords: F14; 330; export margins; East Germany; West Germany; decomposition analysis